2021
DOI: 10.1016/j.isci.2021.102950
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic investigation of multiple methicillin-resistant Staphylococcus aureus strains generated through adaptive laboratory evolution

Abstract: Summary Recent discoveries indicate that tolerance and resistance could rapidly evolve in bacterial populations under intermittent antibiotic treatment. In the present study, we applied antibiotic combinations in laboratory experiments to generate novel methicillin-resistant Staphylococcus aureus strains with distinct phenotypes (tolerance, resistance, and suppressed tolerance), and compared their proteome profiles to uncover the adaptation mechanisms. While the tolerant strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 98 publications
(112 reference statements)
3
32
0
Order By: Relevance
“…Because a larger set of possible mutations are associated with tolerance compared to that associated with resistance, tolerance mutations should appear more frequently and thus earlier in the evolutionary process ( 1 , 2 , 57 ). Mutations leading to daptomycin resistance are restricted to several genes, such as mprF (the most prevalent), cls , walKR , and the dlt operon, which all caused the repulsion of daptomycin from binding to the cell membrane ( 58 ), whereas daptomycin-tolerance mutations were observed in a wide range of genes not necessarily directly related to the action mechanism of the antibiotic (those found in this study, such as prkC , prs , addB , rpsR , and proP , and also those identified in other studies, such as pgsA [ 14 ], pitA [ 17 ], rpoC and purR [ 59 ], snoF , hmp1 , sspA , and many more [ 60 ]). Therefore, in our evolution experiments performed on exponential-phase cultures that eventually led to resistance, we should also expect tolerance mutations to have emerged earlier in the populations.…”
Section: Observationsupporting
confidence: 65%
See 3 more Smart Citations
“…Because a larger set of possible mutations are associated with tolerance compared to that associated with resistance, tolerance mutations should appear more frequently and thus earlier in the evolutionary process ( 1 , 2 , 57 ). Mutations leading to daptomycin resistance are restricted to several genes, such as mprF (the most prevalent), cls , walKR , and the dlt operon, which all caused the repulsion of daptomycin from binding to the cell membrane ( 58 ), whereas daptomycin-tolerance mutations were observed in a wide range of genes not necessarily directly related to the action mechanism of the antibiotic (those found in this study, such as prkC , prs , addB , rpsR , and proP , and also those identified in other studies, such as pgsA [ 14 ], pitA [ 17 ], rpoC and purR [ 59 ], snoF , hmp1 , sspA , and many more [ 60 ]). Therefore, in our evolution experiments performed on exponential-phase cultures that eventually led to resistance, we should also expect tolerance mutations to have emerged earlier in the populations.…”
Section: Observationsupporting
confidence: 65%
“…Although in most cases we observed that the resistant mutant eventually took over the population (lineages 1 to 3, and lineages 7 to 9) and could invade the tolerant mutant (lineage 2), this evolutionary pathway is not always taken. In a previous study, we also observed a situation where a daptomycin tolerance mutation (several base pairs upstream of the pgsA gene) that appeared after a week of cyclic daptomycin treatment was retained in the population even after the evolution experiment was extended for 2 weeks, without being replaced by a resistance mutation ( 14 ). We rationalized that this is because the survival advantage conferred by the mprF resistance mutation is lower than that of the pgsA tolerance mutation (the mprF mutation led to an ∼40-fold increase in survival, whereas the mutation upstream of pgsA led to an over 100-fold increase in survival upon 3 h of 10 mg/liter daptomycin treatment, which was the condition used during the evolution experiment).…”
Section: Observationmentioning
confidence: 79%
See 2 more Smart Citations
“…We adopted a previously described sample preparation workflow that maximize protein identification on S. aureus samples, including the extraction of surface-associated proteins ( 54 ). The cell pellet was suspended in 350 μL lysis buffer (8 M urea, 50 mM Tris-HCl [pH 8.0]), frozen in liquid nitrogen, and sonicated for 15 min.…”
Section: Methodsmentioning
confidence: 99%